Statistical Downscaling for Hydrological and Environmental Applications - Lee, Taesam; Singh, Vijay P.; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
This book presents statistical downscaling techniques in a practical manner so that readers can easily adopt the techniques for hydrological applications and designs in response to climate change. It also provides numerous examples and background information on reliability of impact assessments of climate change and what the results imply.
1. Introduction -- 2. Statistical Background -- 3. Data and Format Description -- 4. Bias Correction -- 5. Regression Downscalings -- 6. Weather Generator Downscaling -- 7. Weather-Type Downscaling -- 8. Temporal Downscaling -- 9. Spatial Downscaling
Includes bibliographical references and index.
Also available in print format.
Keywords: TECHNOLOGY & ENGINEERING / Environmental / General; TECHNOLOGY & ENGINEERING / Environmental / Water Supply; Nonlinear Regression Modeling; Time series modeling; Nonparametric Weather Generator (NWG).; Probability and Statistics; Probabilistic Theory; Discrete Probability Distributions; Continuous Probability Distributions; Multivariate Random Variables; Monte Carlo Simulation; Meta-heuristic Algorithm; Quantile Mapping; Hydrometeorology -- Statistical methods; Multiscale modeling; Electronic books